PROBABLE PROCESSES OF THE ABIOGENIC SYNTHESIS OF BIOLOGICALLY SIGNIFICANT COMPOUNDS AT THE SURFACE OF MINOR BODIES IN THE SOLAR SYSTEM - Simakov M.B.; Kuzicheva E.A. (My University, 2004)
Study of the impact of charged particles, ultra-violet radiation with different wave lengths, and other space energy sources on the abiogenic synthesis of biologically significant compounds (BSC) is closely related to exobiological investigations in the Earth's orbit and the issue of the origin of life on Earth and throughout the universe. According to recent views, the majority of biologically significant compounds bay have been introduced to the primeval Earth by micrometeorites, meteorites, and comets. These cosmic objects contain large quantities of complex organic compounds, including carbohydrates, amino acids, and heterocyclic bases of nucleic acids. Evidently, the chemical evolution proceeds under conditions of open space, which serves as a huge chemical reactor. The aim of this work is to study the dependence of oligopeptide synthesis on proton energy and irradiation dose. The reaction of nucleoside phosphorylation in the presence of inorganic phosphate with phosphate with the formation of nucleotides-the main components of RNA and DNA-under the influence of various energy sources in open space is another important process of chemical evolution. We also attempted to study the impact of mineral substrates on this reaction under the influence of vacuum ultraviolet (VUV) irradiation, one of the main energy sources of the Sun, which represents a powerful source of radiation with wave lengths <200 nm and fluxes of charged particles.